Liberating the liberated : early Śaiva tantric death rites - Mirnig, Nina, 1982- (Sitzungsberichte (Österreichische Akademie der Wissenschaften. Philosophisch-Historische Klasse), 2018)
This volume examines the formation and development of Saiva tantric funerary practices (antye??i) and rituals of post-mortem ancestor worship (?r?ddha) as preserved in the earliest extant strata of textual sources. These tantric scriptures and ritual manuals of the Saiva Siddhanta cover a period from about the 5th to the 12th century CE. A close analysis of individual texts shows how the incorporation of death rites into the tantric repertoire was directly linked to the tradition?s development from once focused on private worship and limited to ascetics living outside society to a dominant religion throughout the Indic world. A focal point of the study is how, in this process, Saiva ritual specialists catered to initiates who were established in the brahmanical householder society, with their death rites essentially coming to serve as the model for Saiva equivalents. To make these rites more meaningful in terms of Saiva doctrine, cremation and post-mortem ancestor worship were redefined as a means for liberating the deceased person?s soul, this through its funerary initiation and subsequent worship in manifestations of increasingly potent forms of Siva.